A one-step SC-CO2 assisted technique to produce compact PVDF-HFP MoS2 supercapacitor device. (January 2020) - Sarno, Maria; Baldino, Lucia; Scudieri, Carmela; Cardea, Stefano; Reverchon, Ernesto
Abstract: Safety, easiness, and ecologically friendly preparation methods are key features in the fabrication of a portable supercapacitor. In this work, it is reported the use of supercritical CO2 (SC–CO2 )-assisted gel drying for the direct preparation in a one-step of a novel porous and portable supercapacitor device. It consists of three layers, grown together and able to uptake a large amount of an ionic liquid, of an aerogel of Poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP): the middle layer is formed by PVDF-HFP alone and the top, and bottom layers are formed by PVDF-HFP aerogels containing dispersed molybdenum disulfide (MoS2 ) nanosheets (i.e., PVDF-HFP + MoS2 ). The produced supercapacitor device (PVMS) is characterized by a mesoporous structure with high surface area, taking advantage from both non-flammability and electrochemical stability of PVDF-HFP and high capacitance of MoS2 due to its fast ionic conductivity. The supercapacitor, at the optimized operative conditions, achieves an excellent specific capacitance of 176 F/g and a very high energy density of 97.8 Wh/Kg at a power density of 0.65 of kW/kg (current density 0.6 A/g), that still remains 76.4 Wh/kg at 5.1 kW/kg (current density 5 A/g, specific capacitance of 138.2 F/g). The device shows good stability in an ionic liquid electrolyte, suggesting that the proposed process can be a new opportunity to produce highly bulky improved supercapacitors. Highlights: Supercritical CO2 -assisted for direct synthesis in a one-step. Portable supercapacitor device. Favorable porosity. High specific capacitance and good rate capability.